Factores asociados con la participación electoral en Colombia (2020)
Electoral participation in Colombia has been a subject of study, not only because of democratic processes throughout history but also because of the history of Colombians about it. With information about the presidential elections for the election periods between 2006 -2014, this article studies how some demographic, economic and social factors of the electoral participation rate. The methodology implemented consists of an economic data panel model, taking into account information related to the electoral participation rate by department, socio-demographic rates and economic growth data. It was found that most of the variables that the objects of study relate positively with the percentage of consumers, such as the growth of each state, which is the participation rate, education, and negatively with poverty.